Estudo de caso: análise de exposição a riscos de trabalhadores externos da CAERN - Regional Alto Oeste - Ribeiro, David Menson Bezerra (Universidade Federal Rural do Semi-Árido, 2017)
The Water and Sewage Company of the RN (Companhia de Águas e Esgotos do RN - CAERN) is composed by administrative workers (internal) and field workers (external). The company is responsible for the distribution of water and sewage collection and treatment throughout the RN. The regional CAERN of Pau dos Ferros serves 34 citys, which are Pau dos Ferros and 33 other ones close to headquarters, totaling 109 external workers, in different age groups and levels of education according to the position requirement in public tender, which could vary from fundamental level to superior level. External workers conduct their activities outside the headquarters physical structure. They are subject to various environmental risks on his routine. In this work, the activities of a external employees group of the company were monitored through the use of devices to measure the conditions of exposure to luminosity, solar energy and noise, and the visit and recognition of working environment conditions. The complementation with bibliographical research, facilitate the observation of some environmental risks the workers are exposed to, to analyze them and to propose solutions for the improvement of occupational safety of this employees. Through this characterization of the work environment, it was possible to compare the conditions of exposure provided for the Regulatory Rules(Normas Regulamentadoras – NR) with the ones the employees are submitted, and also to verify the salubrity level of the work environment. The external workers are more exposed to sunlight, solar energy, machinery noise, accidents due to material falls and falls from a height, cuts and stings of insects and venomous animals, and chemical, biological and even ergonomic risks. In order to carry out the activities correctly, safely and effectively some types of training are required and must be provided by the company, as well as implement Individual and Collective Protection Equipment, to better inform the workers and reduce exposure to the risks that exists.
Keywords: Riscos ambientais; trabalhadores externos; segurança do trabalho; environmental risks; external workers; occupational safety; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA